Morphological identification of the squirrel (Callosciurus notatus) tongue through Scanning Electron Microscopy (SEM) and histochemistry - EMILIA IKA MEGAWATI; STANISLAUS IVAN DAVIN PRADIPTA; ULFAH DAMIA; ULAYATUL KUSTIATI; HEVI WIHADMADYATAMI; DWI LILIEK KUSINDARTA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Megawati EI, Pradipta SID, Damia U, Kustiati U, Wihadmadyatami H, Kusindarta DL. 2023. Morphological identification of the squirrel (Callosciurus notatus) tongue through Scanning Electron Microscopy (SEM) and histochemistry. Biodiversitas 24: 2302-2314. Squirrel (Callosciurus notatus) plays an important role in the agricultural ecosystem.Their urine and feces kill coconut tree pests and help preserve coconut farming productivity. This research focuses on the morphological identification of the tongue and lingual papillae distribution of the Callosciurus notatus’stongue. The tongue morphology and lingual papillae distribution of Callosciurus notatus were investigated through two different methods: using scanning electron microscopy (SEM) and histology. This paper provides macroscopic and histological tongue morphology and lingual papillae distribution of Callosciurus notatus. Macroscopically, the tongue is divided into the apex, corpus, and radix. The dorsal surface of the apex the groove and lateral prominence were occur. SEM and light microscopy observation showed that the apex bears three types of papillae: leaf-like filiform, bifid filiform, and fungiform. The corpus includes wide leaf-like filiform papillae, saw-like filiform papillae, bifid filiform papillae, and fungiform papillae. On the radix, there are conical like filiform papillae, fungiform papillae, conical and vallatae papillae. The lateral part of radix showed Weber’s glands that react strongly positively by Alcian Blue (AB) pH 2.5 and periodic acid Schiff (PAS) staining; Weber’s glands consist of neutral and acidic mucin. Von Ebner’s glands were at the textus muscularis striatus syncytialis near the vallatae papillae, which react weakly positively to PAS stain and did not react to AB pH 2.5 stain; von Ebner’s glands consist of neutral mucin. Masson Trichromestain revealed collagen structure on lamina propria mucosae and textus muscularis striatus syncytialis of apex; moderately on lamina propria mucosae and lesser on textus muscularis striatus syncytialis of the corpus and radix.